2004
DOI: 10.1002/chir.20048
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of highly optically pure homochiral sulfide‐containing alcohols via oxazaborolidine‐catalyzed asymmetric borane reduction of ketones

Abstract: Highly optically pure homochiral 1-(4-alkylthiophenyl) alcohols were prepared efficiently and practically via the oxazaborolidine-catalyzed asymmetric borane reduction of prochiral ketones in toluene at 25 degrees C. The coordination of the sulfur atom in the ketones to the boron atom in the catalyst and borane can be inhibited under these reduction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…Many chiral 1,3,2-oxazaborolidines derived from chiral vicinal amino alcohols have been prepared and evaluated in the asymmetric borane reduction of ketones, and some of the best enantioselectivities have been achieved with them . Among them, ( S )-2-substituted 4,4-diphenyl-3,1,2-oxazaboro[3.3.0]octanes 1 , derived from ( S )-2-(diphenylhydroxymethyl)pyrrolidine, with several different substituents (such as H for 1a , Me for 1b , Ph for 1c , and MeO for 1d , as representatives, Scheme ) on the B atom, have been proven to be effective catalysts in the asymmetric reduction with excellent yields and enantioselectivities for a wide variety of ketones. ,, However, 1a and 1b are not entirely satisfactory, particularly for large-scale productions, owing to the necessity of relatively expensive reagents, such as trimethyl boroxin or methylboronic acid, for their preparation 3 and the necessity of the preparation before catalytic reactions in order to get excellent and stable enantioselectivity. Furthermore, the catalyst 1a is air and moisture sensitive .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many chiral 1,3,2-oxazaborolidines derived from chiral vicinal amino alcohols have been prepared and evaluated in the asymmetric borane reduction of ketones, and some of the best enantioselectivities have been achieved with them . Among them, ( S )-2-substituted 4,4-diphenyl-3,1,2-oxazaboro[3.3.0]octanes 1 , derived from ( S )-2-(diphenylhydroxymethyl)pyrrolidine, with several different substituents (such as H for 1a , Me for 1b , Ph for 1c , and MeO for 1d , as representatives, Scheme ) on the B atom, have been proven to be effective catalysts in the asymmetric reduction with excellent yields and enantioselectivities for a wide variety of ketones. ,, However, 1a and 1b are not entirely satisfactory, particularly for large-scale productions, owing to the necessity of relatively expensive reagents, such as trimethyl boroxin or methylboronic acid, for their preparation 3 and the necessity of the preparation before catalytic reactions in order to get excellent and stable enantioselectivity. Furthermore, the catalyst 1a is air and moisture sensitive .…”
Section: Resultsmentioning
confidence: 99%
“…Numerous new efficient oxazaborolidines as catalysts have been reported and a plethora of applications have appeared until now. In comparison with the numerous attempts to search for new catalysts and to improve the enantioselectivity, several papers have concentrated on the mechanistic investigation of the catalytic asymmetric reduction reaction, , and some papers have paid attention to the factors which affect the enantioselectivity in the asymmetric reduction, such as the structure, ,, stability 3a,6 (including dimerization) and the amount of the catalyst, 3a,6a, the borane source 8 and the borane amount, 3a,7c the order and rate of the addition of a ketone or borane into the reductive system, 2d,7c the reduction temperature, 7c, solvent, 6a,7c,8c additive, 9g, secondary reduction, 10a, and stabilizer in borane, etc. Although a few papers have considered the influence of the electronic effects of ketones and catalysts on the enantioselectivity, all of the results indicated that no obvious influence has been observed in the asymmetric reduction 5a,6a,13 except for the observation of Corey et al13c Very recently we investigated the temperature-dependent enantioselectivity of the asymmetric reduction and found that the noncatalytic reduction is an important factor for the enantioselectivity in asymmetric reductions 7c.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1-(4-(Heptylthio)phenyl)ethanone (3ab): [13] Colorless liquid, 207 mg, 94% yield. 1 H NMR (500 MHz, CDCl 3 ) δ: 7.86 (d,J=8.5 Hz,2H), 7.30 (d,J=9.0 Hz,2H) 196.9, 144.3, 134.0, 128.6, 128.1, 48.1, 32.5, 26.3, 19.9, 18.4, 16.9;IR (neat) ν: 2966IR (neat) ν: , 2940IR (neat) ν: , 2874IR (neat) ν: , 1680IR (neat) ν: , 1589IR (neat) ν: , 1552IR (neat) ν: , 1394IR (neat) ν: , 1350IR (neat) ν: , 1262IR (neat) ν: , 1181IR (neat) ν: , 1097, 601 cm -1 ; HRMS (EI) calcd for C 13 H 18 SO: 222.1078, found 222.1080.…”
Section: General Procedures For the Coupling Reaction Of Aryl Bromidesmentioning
confidence: 99%
“…, 2.99 (t, J=7.5 Hz, 2H), 2.57 (s, 3H), 1.73~1.66 (m, 2H), 1.46~ 1.43 (m, 2H), 1.34~1.26 (m, 6H), 0.89 (t, J=7.0 Hz, 3H).1-(4-((3-Methylbutan-2-yl)thio)phenyl)ethanone (3ac): Colorless liquid, 162 mg, 84% yield. 1 H NMR (500 MHz, CDCl 3 ) δ: 7.85(d, J=8.5 Hz, 2H), 7.35(d, J=8.5 Hz, 2H), 3.39~3.34 (m, 1H), 2.55 (s, 3H), 1.98~1.92 (m, 1H), 1.30(d, J=7.0 Hz, 3H), 1.04~1.00 (m, 6H);13 C NMR (125 MHz, CDCl 3 ) δ:…”
mentioning
confidence: 99%